What have we learnt from the uses and abuses of options in corporate risk management - Ramiah Vishal (2008)
This paper provides details on the value creation process of risk management, the various types of risks that non financial firms face and further elaborates on the various tools to manage these risks. Thereafter, the paper investigates the motivations and practice of non-financial firms with regard to using options in their risk management activities. To this end, it provides a comprehensive account of the existing empirical evidence on the use of options in particular by non-financial corporations across different underlying and countries.